Critical Thinking on the Determinants Matrix: The Development of A Teaching Module - Kosasih, Usep; Sumartana, Ammar Hanif; Sulastri, Yayu Laila; Ahmatika, Deti; Ramandhita, Annisa Tri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This research is motivated by the unavailability of determinant matrix teaching materials that meet students' needs and curriculum standards and students' low critical thinking skills, so a determinant matrix teaching module is needed that complies with curriculum standards and facilitates critical thinking skills. Teaching modules are developed using the Project-Based Learning model. This mixed-methods research aims to determine teaching modules' validity, practicality, and effectiveness. This article is a design research report using the Plomp model. The data sources in this research are material expert validators, media experts, educational practitioners, and respondents. The instruments used are validity sheets for material experts, media experts, description tests, observation of the learning process, and critical thinking ability tests. The results of data analysis in this research concluded that the teaching module that had been developed was very valid, practical, and effective. The developed instructional materials are believed to support learning that emphasizes critical thinking. In conclusion, the teaching materials incorporate exercises that enhance critical thinking skills using case presentations. Furthermore, it is suggested that the module be used as an alternative teaching tool and that further research be done with different data, materials, or other mathematical abilities.